Antagonism between SUMO1/2 and SUMO3 regulates SUMO conjugate levels and fine-tunes immunity. (18th June 2021) - Ingole, Kishor D; Kasera, Mritunjay; van den Burg, Harrold A; Bhattacharjee, Saikat
Abstract : SUM1/2 suppress antibacterial immunity, whereas SUM3 stimulates these processes. Basal SUM3 levels and its induction during pathogen attack or heat shock modulates SUMO1/2 conjugate levels, suggesting that SUMO3 acts as an agonist of SUMO1/2-ylation. Abstract: The attachment of SMALL UBIQUITIN-LIKE MODIFIER (SUMO) to target proteins regulates a plethora of cellular processes across eukaryotes. In Arabidopsis thaliana, mutants with abnormal SUMO1/2 conjugate levels display a dwarf stature, autoimmunity, and altered stress responses to adverse environmental conditions. Since the SUMO pathway is known to autoregulate its biochemical activity (via allosteric interactions), we assessed whether the emergence of additional SUMO paralogs in Arabidopsis has introduced the capacity of self-regulation by means of isoform diversification in this model plant. By studying the plant defense responses elicited by the bacterial pathogen Pseudomonas syringae pv. tomato, we provide genetic evidence that SUM3, a divergent paralog, acts downstream of the two main SUMO paralogues, SUM1/2 . The expression of SUM3 apparently buffers or suppresses the function of SUM1/2 by controlling the timing and amplitude of the immune response. Moreover, SUM1 and SUM2 work additively to suppress both basal and TNL-specific immunity, a specific branch of the immune network. Finally, our data reveal that SUM3 is required for the global increase in SUMO1/2 conjugates upon exposure to biotic and abiotic stresses, namely heat and pathogen exposure. We cannot exclude that this latter effect is independent of the role of SUM3 in immunity.